KOLABORASI PENGURUS DAN GEN Z DALAM TATA KELOLA MASJID SECARA MODERN - Rina Gusmawati; Noor Fadlli Marh (Irfani, 2025)
This paper is motivated by the mosque's long-neglected and deserted presence, leading to its limited access to worshippers during the Maghrib and Isha prayers. This is evidenced by the mosque's frequent locking after Isha prayers and reopening at Maghrib. This study aims to uncover the causes of the mosque's neglect and lack of worshippers. This type of research uses the descriptive qualitative method used by researchers is to describe and present results that are in accordance with the information and data obtained in the field regarding the collaboration between administrators and Gen Z in modern mosque governance. The research location is the Nurul Firdaus Mosque, Padang Ranjau, Jorong Binjai, Tigo Nagari District, Pasaman Regency. The data collection techniques used by researchers are interviews and documentation. Research informants consist of religious leaders, community leaders, mosque administrators, mosque youth, and the community. The theory used in this study is Anthony Giddens' theory. The results of this study are to show the collaboration of mosque administrators and youth in mosque governance where the mosque has long been neglected and deserted by the congregation due to the administrators' indifference and neglect regarding the responsibilities that have been given to the community.